Chinese Herbal Medicine for Treating Epilepsy - Lin, Chia-Hui; Hsieh, Ching-Liang (Frontiers in Neuroscience, 2021)
Chinese herbal medicine has a long history of use for treating epilepsy. Because of the side effects of Western antiepileptic therapy and the quest for more accessible treatment, complementary and alternative medicines have become popular. Traditional Chinese medical diet therapy appears to be safe and effective. We searched PubMed and Cochrane Library until November 2020 for the commonly used traditional Chinese medicine in clinical settings, including plants, fungi, and animals. The various combinations of keywords included “epilepsy,” “seizure,” “antiepileptic,” “anticonvulsive,” “Chinese herbal medicine,” “Chinese herb,” and each of the Latin names, English names, and scientific names of herbs. We also summarized the sources and functions of these herbs in Chinese medicine. Different herbs can be combined to increase antiepileptic effects through various mechanisms, including anti-inflammation, antioxidation, GABAergic effect enhancement, modulation of NMDA receptor and sodium channel, and neuroprotection. Despite reports of their anticonvulsive effects, adequate experimental evidence and randomized controlled clinical trials are required to confirm their antiepileptic effects.